Seeking Accountability for Nazi and War Crimes in East and Central Europe : A People's Justice? - Voisin, Vanessa (Book collections on Project MUSE., 2022)
The thirst for post-World War II justice transcended the Cold War and mobilized diverse social groups. This is a story of their multilayered and at times conflictual interactions.